NONCHEMICAL VERSUS CHEMICAL PROTECTION IN POTATO BLIGHT - György SZABÓ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to broadly present the specific issues connected to potato cultivation. There are approached aspects of those issues that are not examined enough or the issues which are not yet solved, namely plant nutrient disorders caused by plant protection. There is a specialised field of work concerned with the above topic, but the efficient solutions are few. The majority of solutions recommend chemical intervention, but this does not compile with the recent orientations regarding the EU new Common Agricultural Policy reform expresses in Green Deal that points out the need as production technologies to be environmentally friendly and products to be healthy for assuring food safety. For this reason, in the paper it is presented a biological environmental protection solution in potato cropping for Ila variety compared to chemical protection applied to Kloepatra variety.